Patterns of use of palliative radiotherapy fractionation for bone metastases and 30-day mortality. (January 2021) - Batumalai, V.; Descallar, J.; Delaney, G.P.; Gabriel, G.; Wong, K.; Shafiq, J.; Vinod, S.K.; Barton, M.B.
Highlights: SFRT is underused for the treatment of bone metastases in NSW. An estimated two in every three patients received MFRT. Variation were observed by patient, sociodemographic and geographical factors - The 30-day mortality rate after SFRT was higher than multi-fraction RT. Policy changes are needed such that SFRT is the default norm. Abstract: Background and purpose: Adoption of single-fraction radiation therapy (SFRT) has not been universal in the palliative treatment of bone metastases, despite evidence supporting its safety and efficacy. The aim of this study was to assess SFRT use for bone metastases in New South Wales (NSW), Australia, and the rate of 30-day mortality (30DM). Materials and methods: This is a population-based cohort of patients who received palliative radiation therapy (RT) for bone metastases (2009–2014), as captured in the NSW Central Cancer Registry. A logistic regression model was used to identify factors associated with fractionation type. The proportion of patients dying within 30-days from treatment start date was calculated. Results: Of the 14, 602 courses of palliative RT delivered for bone metastases, 30% were SFRT. SFRT was more likely to be delivered to older patients: ≥80 years (34%) versus < 60 years (28%). Patients with lower socioeconomic status (SES) (35%) were more likely to receive SFRT compared with higher SES (25%). SFRT delivered to patients from outer regional area of residence (34%) were higher compared to those from the major city (29%). The proportion of SFRT delivered to patients with comorbidities ≥2 (34%) was higher than patients with no comorbidity (29%). SFRT was associated with higher 30DM of 21% compared with 11% for multi-fraction RT (MFRT). Conclusion: SFRT is underused for the treatment of bone metastases in NSW. This is an impetus to develop tools making SFRT obligatory in this setting unless there is good justification not to.